The challenges in the reading of legal cases: lecturers' perspective - Ariffin, Adlina; Mohd. Asraf, Ratnawati (2014)
The ability to read legal cases is one of the most essential skills for law students to be successful in their discipline. It is particularly fundamental since case law is one of the main sources of law. Christensen (2007) in her research entitled "Legal Reading and Success in Law School: An Empirical Study" shows that students who are able to read judicial opinions effectively and efficiently are more successful in their studies. Upon realizing the fundamental role of this legal skill to law undergraduates, a study was conducted to look at the pedagogical and methodological perspectives in the teaching of this skill at a law faculty in a Malaysian public university. Among the aims of this research were to uncover the problems related to the teaching process as well as illuminate some practical suggestions to enhance the quality in teaching this particular legal skill. This study which adopted an in-depth case study design obtained the data through interview sessions with six law students and three law senior lecturers. The major findings are divided into two categories- lecturers’ perceptions on law students and lecturers’ perceptions on the management of the legal skill courses.